RESISTENSI FIXED MINDSET DALAM MEMENGARUHI KESADARAN MASYARAKAT TERHADAP PENDIDIKAN - Faizah; Ari Reski Sashari; Saiful; Rina Asriani Bakri (Almeera Education, 2023)
Education in general is very important to create human beings with character, but it turns out that the Bontokamase people still don't understand the importance of education, the lack of awareness of the Bontokamase people towards education is due to their established level of economic growth. ) then the mindset that is built related to education is only limited to being good at reading, counting, and writing. The purpose of this research is to add to the study, especially Fixed Mindset Resistance in influencing public awareness of education. This type of qualitative research is the result of field research and uses a sociological approach. The results of the study showed that the factors that caused the Bontokamase community to have a low level of education awareness were the hereditary factors that their parents had never attended school but that did not mean they were incapable financially, financially they were able to go to school but the cause was that they do not go to school because they have a large area of agricultural land to work on and according to them the results are more promising compared to studying which takes a long time and it is also difficult to get a job. Diplomas are only a formality in getting a job, diplomas no longer have anything to do with intelligence, graduates become unemployed because it is difficult to get a job with a diploma so this becomes a reference that education is not a guarantee of one's success.